Reasons fostering or discouraging the implementation of central bank-backed digital currency: A review - Sergio Luis Ná\~nez Alonso; Miguel Ángel Echarte Fernández; David Sanz Bas; Jarosław Kaczmarek (Economies, 2020)
This study analyses the current debate around central bank-backed digital currency (CBDC). A comparative study was carried out considering countries for and against implementing a CBDC and their reasons, looking for common causes, differences, etc. The conclusion was that there are opposite tendencies between defenders and detractors of establishing a CBDC. However, today-and taking into account the positions of three large banking institutions (the Federal Reserve of the United States of America, the Bank of Japan and the Bank of England) on establishing (at least in the short term) a CBDC)-it seems that large-scale implementation is still far off. On the contrary, the Chinese Central Bank and banking systems of other countries that have less weight in the world, such as Uruguay, Lithuania and the Bahamas, seem to go against the trend of rejection and are seriously considering its implementation. Although this matter has been dealt with in the theoretical field, more pilot tests such as the one carried out by Uruguay are necessary in order to understand specific effects on the economy, on one hand, and on acceptance of its use by the population, on the other.
Keywords: E52; E58; E59; 330; CBDC; digital currency; monetary policy